Improving the efficiency of the system of taxation of the oil and gas sector in Russia: main tendencies, prospects and limitations - V. A. Kulakovskaya (Новые технологии)
The oil and gas industry plays an important role in the economy of the Russian Federation (hereinafter referred to as the RF). This sector contributes to the formation of gross domestic product (hereinafter referred to as GDP) and the revenues of the state budget of the country. In this regard, work was carried out to identify ways to improve the efficiency of the tax system of the oil and gas sector of our country. The object of the research is social relations arising in connection with the taxation of the oil and gas sector of the RF. The subject is the taxation system of the oil and gas sector. The research provides general information about the position of our country in the overall ranking of countries in terms of mining, consumption, and oil and gas reserves. The concession taxation model of the oil industry is considered, as well as the advantages and disadvantages of charging lump-sum taxes. The major disadvantages of the current tax system in the oil and gas sector in Russia are described, and a range of measures for its improvement are proposed. Scientific works on the taxation of the oil sector in Russia make up the theoretical basis of the research. Political journalism, reference books and statistical materials make up the empirical basis. In the process of preparing the essay, along with works on taxation of the oil sector, sociological and other literature on the research topic was used in the work. Reliability and validity of the research results are provided with a theoretical analysis of the works of domestic and foreign authors, using methods that correspond to the objectives of the study.